Effect of azithromycin on post-discharge growth in Kenyan children - Atlas, Hannah E; Mogeni, Polycarp; Shawon, Riffat Ara; Tickell, Kirkby D; Bunyige, Lucy; Monchari, Irene; Oongo, Susan; Diakhate, Mame M; Brander, Rebecca L.; Liru, Meshack; Bogonko, George; Nduati, Ruth; et al. (BMJ, 2025)
Introduction: Children discharged following hospitalisation for acute illnesses in low- and middle-income settings are at increased risk of poor growth, particularly linear growth faltering. We aimed to determine the effect of azithromycin administered at hospital discharge on post-discharge growth.